Numerical study on factors affecting the induction of apoptotic temperatures of tumor in the multi-layer skin structure using Monte Carlo method - Kim, Donghyuk; Kang, Sukkyung; Kim, Hyunjung (Applied Sciences (Switzerland), 2021)
The incidence of skin cancer is increasing with the recent increase in UV exposure. The treatment of skin cancer generally proceeds through an excision of the tumor area, which causes bleeding into the affected area and surrounding tissues, and there is a possibility that secondary infection may occur. Photothermal therapy is drawing attention as an alternative treatment to over-come this limitation. In this study, a numerical analysis was performed on skin cancer tumors located between the reticular dermis and the skin surface by applying the Monte Carlo method. The numerical analysis derives a quantitative correlation using an effective apoptosis ratio with respect to the intensity of the laser that produces the optimal photothermal therapy effect and the volume fraction of gold nanorods (GNRs) injected into a tumor. Through this study, it is confirmed that the optimal treatment effect exists for the depth and length of the various tumors, the intensity of the laser, and the volume fraction of GNRs to minimize the thermal damage to the surrounding normal tissues while maximizing the apoptosis in the tumor. It is expected that it can be used as an optimal condition for better treatment while performing photothermal therapy in the future.
Keywords: Apoptosis; Gold nanoparticles; Heat transfer; Hyperthermia; Monte Carlo method; NIR laser; Photothermal therapy; Skin cancer; Skin layer; Thermal damage